Morphological Causative Construction of Indonesian and Javanese: A Typological Study - Siti Nur Hasisah; Agus Subiyanto; Ahmad Abu Rifai (PAROLE: Journal of Linguistics and Education, 2021)
This study proposes to describe morphological causative formation in Indonesian and Javanese to determine similar verbs by comparing both. The levels of causative formation patterns in the Rembang Javanese dialect and Indonesian include (1) analytical causative construction, (2) morphological causation, and (3) lexical causation. This study focuses on the morphological causative construction in both languages. This study is descriptive qualitative with a language typology approach. Sources of data came from oral and written data. The data analysis applied typology theory. The results point out that the morphological causative form in Indonesian is constructed with the suffix “-kan” only. Meanwhile, Rembang Javanese dialect is much greater; it can be formed with the prefix “n-“, infix “-en”, infix “-in”, the suffix “-I”, the suffix “-no”, and the suffix “–ke”. These affixes increase the number of valences (arguments).